Representasi Kemuliaan Seorang Ibu Perspektif Budaya Madura dalam Puisi D. Zawawi Imron: Kajian Semiotika Roland Barthes - Hayyul Mubarok; Setya Yuwana Sudikan; Suhartono (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study reveals the representation of the nobility of a mother in poetry by D. Zawawi Imron through the perspective of Madurese culture with Roland Barthes' semiotic approach. The analyzed poems, especially the poem entitled